Factors Influencing Organisational Citizenship Behaviour of Information Technology Professionals in Chennai, India - Srividya, P (2023)
Organization is one of the vital economic factors which coordinates the rest of the other factors such as land, labour and capital. The best organization structure reveals the successful business environment. In a dynamic environment adhered by globalisation, the major challenge for human resource upshots in gaining organizational competitive advantage. The investment scenario of the organisation largely depends on its employee performance as well as citizenship behaviour of the employees. Questionnaire was administered to 834 sample respondents chosen by simple random method. Five-Point Likert Scaling method was used to gather opinion of the respondents regarding constructs of the study. Structural Equation Modelling was used to examine the hidden relationship among the constructs of the study. The study found that personality and organizational commitment has significant effect on overall OCB and overall OCB has significant and positive impact on organizational performance.